Successful External Cardioversion via Fluoroscopic Electrode Positioning in Patients with Enlarged Trans-Thoracic Diameter - Khalighi, Koroush (Am J Case Rep, 2018)
Case series Patient: Female, 71 • Male, 48 • Male, 74 Final Diagnosis: Failed cardioversion Symptoms: Dizziness • dyspnea • fatigue • palpitations Medication: Ace Inhibitors • Beta Blockers • Calcium Channel Blockers • Dronedarone • Novel Oral Anticoagulants • Warfarin Clinical Procedure: Fluoroscopic cardioversion • radiofrequency catheter ablation Specialty: Cardiology OBJECTIVE: Unusual setting of medical care BACKGROUND: Atrial fibrillation is the most common cardiac arrhythmia. It increases the risk of stroke by at least five-fold and is associated with higher risk for mortality and morbidity. Therefore, prompt diagnosis and treatment is crucial. In addition to anti-coagulation therapy, electrical and pharmacological cardioversion to restore sinus rhythm remains the standard of care. The most common and effective method for electrical cardioversion is achieved with placement of electrodes in the anteroposterior position. CASE REPORT: We present three cases of patients with initial unsuccessful cardioversion attempts for persistent atrial fibrillation. These patients had elevated body mass indices and large trans-thoracic diameters. Their initial external cardioversion via the conventional method was not successful for restoration of sinus rhythm. This failure may have been attributed to their body habitus. To ensure that the current would traverse through the atrial tissue, the electrode pads were applied using fluoroscopic guidance for adequate myocardial depolarization. CONCLUSIONS: Optimal fluoroscopic placement of the electrode pads during external cardioversion procedure increases the odds of successful restoration of sinus rhythm when compared to the conventional method.